2018
DOI: 10.1186/s13012-018-0721-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of inter-organizational alignment (IOA) on implementation outcomes: evaluating unique and shared organizational influences in education sector mental health

Abstract: BackgroundIntegrated healthcare delivered by work groups in nontraditional service settings is increasingly common, yet contemporary implementation frameworks typically assume a single organization—or organizational unit—within which system-level processes influence service quality and implementation success. Recent implementation frameworks predict that inter-organizational alignment (i.e., similarity in values, characteristics, activities related to implementation across organizations) may facilitate the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 104 publications
(109 reference statements)
0
42
0
Order By: Relevance
“…The codebook template was used to understand the multilevel determinants of implementation. Determinants include aspects of the innovation (eg, evidence strength and relative advantage), outer context (eg, external policies and incentives), the inner organizational context (eg, implementation climate and tension for change ), characteristics of the individuals operating within target settings (eg, attitudes and efficacy), and process of change in the organization (eg, engagement strategies and change agents) [ 47 - 51 ]. School personnel interviews were audio recorded, transcribed, and coded with directed content analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The codebook template was used to understand the multilevel determinants of implementation. Determinants include aspects of the innovation (eg, evidence strength and relative advantage), outer context (eg, external policies and incentives), the inner organizational context (eg, implementation climate and tension for change ), characteristics of the individuals operating within target settings (eg, attitudes and efficacy), and process of change in the organization (eg, engagement strategies and change agents) [ 47 - 51 ]. School personnel interviews were audio recorded, transcribed, and coded with directed content analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, some studies have found that individual factors (especially attitudes) may be significantly more predictive of the use of EBT than organizational factors (e.g., organizational culture, implementation climate) [23,24]. Although individual attitudes and behaviors are embedded within larger contexts [25], individual barriers This study will be the first to test a pragmatic, theory-driven, and generalizable implementation strategy in the context of improving clinician use of an evidence-based trauma intervention in the education sector, the most common setting for youth mental health service delivery.…”
Section: Multilevel Implementation Determinantsmentioning
confidence: 99%
“…Indeed, some studies have found that individual factors (especially attitudes) may be significantly more predictive of the use of EBT than organizational factors (e.g., organizational culture, implementation climate) [ 23 , 24 ]. Although individual attitudes and behaviors are embedded within larger contexts [ 25 ], individual barriers may be more malleable and proximal to EBT implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Hoover and colleagues (2018) offered a separate four-stage process for implementing an EBP program, Cognitive Behavioral Intervention for Trauma in Schools, which included (a) planning, (b) community buy-in, (c) training, and (d) implementation and support. Other studies have illustrated the intra- and interorganizational process required within schools to successfully implement EBP in mental health, calling for additional interorganizational alignment between schools and outside organizations to guide implementation efforts (e.g., Lyon et al, 2018).…”
Section: Ebp University–practitioner Partnership Modelmentioning
confidence: 99%
“…Bauman et al (2002) found that practitioners cite time constraints and a general dislike for research as reasons for not using literature to guide practice. Further, research in related fields suggests that implementing EBP in school settings is complicated and is best accomplished using intentional frameworks for implementation (Hoover et al, 2018;Lyon et al, 2018;Novins, Green, Legha, & Aarons, 2013). As a result, practitioners' attitudes toward research and evidence, and the lack of intentional frameworks for implementation of evidence-based school counseling, place one of the fields' top priorities (implementing effective school counseling models) in a precarious position.…”
mentioning
confidence: 99%